17β-Estradiol Protects Neural Stem/Progenitor Cells Against Ketamine-Induced Injury Through Estrogen Receptor β Pathway - Li, Weisong; Lu, Pan; Lu, Yang; Wei, Haidong; Niu, Xiaoli; Xu, Jing; Wang, Kui; Zhang, Hong; Li, Rong; Qiu, Zhengguo; Wang, Ning; Jia, Pengyu; et al. (Frontiers in Neuroscience, 2020)
Ketamine inhibits neural stem cell (NSC) proliferation and disturbs normal neurogenesis in the developing brain. 17β-estradiol attenuates neurogenesis damage and improves behavior performance following ketamine exposure. However, the receptor pathway of 17β-estradiol protects NSCs from ketamine-induced injury remains unknown. In the present study, we investigated the role of estrogen receptor α (ER-α) and estrogen receptor β (ER-β) in 17β-estradiol’s protection against ketamine-exposed NSCs and explored its potential mechanism. The primary cultured NSCs were identified by immunofluorescence and then treated with ketamine and varying doses of ER-α agonist 4,4',4''-(4-propyl-[1H]-pyrazole-1,3,5-triyl) trisphenol (PPT) or ER-β agonist 2,3-bis(4-hydroxyphenyl)-propionitrile (DPN) for 24h. NSC proliferation was analyzed by 5-Bromo-2-deoxyUridine (BrdU) incorporation test. The expression of phosphorylated glycogen synthase kinase-3β (p-GSK-3β) was quantified by western blotting. It was found that treatment with different concentration of PPT did not alter the inhibition of ketamine on NSC proliferation. However, treatment with DPN attenuated the inhibition of ketamine on NSC proliferation at 24h following their exposure (P<0.05). Furthermore, treatment with DPN increased p-GSK-3β expression in NSCs exposed to ketamine. These findings indicated that ER-β may mediate the protective effects of 17β-estradiol on ketamine-damaged NSCs proliferation and GSK-3β is involved in this process